2014
DOI: 10.1124/dmd.114.062307
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X Receptor Modulates the Inflammatory Response in Primary Cultures of Hepatocytes

Abstract: Bacterial sepsis is characterized by a rapid increase in the expression of inflammatory mediators to initiate the acute phase response in liver. Inflammatory mediator release is counterbalanced by the coordinated expression of anti-inflammatory molecules such as interleukin 1 receptor antagonist (IL1-Ra) through time. This study determined whether activation of pregnane X receptor (PXR, NR1I2) alters the lipopolysaccharide (LPS)-inducible gene expression program in primary cultures of hepatocytes (PCHs). Preac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 55 publications
(72 reference statements)
1
47
0
Order By: Relevance
“…Expression of exogenous PXR significantly increased the basal levels of TNFa messenger RNA by approximately 8-fold when compared with vehicletreated nontransduced PXR-KO hepatocytes. This is consistent with our previous publication that indicates that hepatocytes lacking PXR exhibit a diminished capacity to mount a robust immune response following challenge with a lipopolysaccharide (Sun et al, 2015). Hepatocytes expressing exogenous PXR that were cotreated with TNFa and rifampicin together exhibited significant repression of TNFainducible TNFa messenger RNA expression.…”
Section: Sumoylation and Ubiquitylation Of Pregnane X Receptorsupporting
confidence: 81%
See 2 more Smart Citations
“…Expression of exogenous PXR significantly increased the basal levels of TNFa messenger RNA by approximately 8-fold when compared with vehicletreated nontransduced PXR-KO hepatocytes. This is consistent with our previous publication that indicates that hepatocytes lacking PXR exhibit a diminished capacity to mount a robust immune response following challenge with a lipopolysaccharide (Sun et al, 2015). Hepatocytes expressing exogenous PXR that were cotreated with TNFa and rifampicin together exhibited significant repression of TNFainducible TNFa messenger RNA expression.…”
Section: Sumoylation and Ubiquitylation Of Pregnane X Receptorsupporting
confidence: 81%
“…Previous research from our laboratory and others indicates that PXR activation can suppress the cytokine-inducible expression of TNFa and interleukin 6 (IL-6) in the liver and intestine (Teng and PiquetteMiller, 2005;Shah et al, 2007;Hu et al, 2010;Dou et al, 2012;Koutsounas et al, 2013;Sun et al, 2015). We therefore examined the role of PIAS1 in promoting this effect in a PXR-dependent manner in the liver.…”
Section: Pxr Is the Molecular Target Of Both The Sumo-andmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the expression of ABC transporter MDR1 and MRP2 is induced by rifampicin via PXR and CAR nuclear receptors [25]. As a consequence, we investigated the involvement of nuclear receptors such as PXR, CAR, AhR and RXRα in regulation of SLC transporters by rifampicin.…”
Section: Rifampicin Regulates Ahr and Rxra Expression In Human Skinmentioning
confidence: 99%
“…In addition, another study reported that PXRs have anti-inflammation functions via suppression of signal transduction pathways (Sun et al, 2015). Although we did not observe the binding of PXR to the clotrimazole-responsive element, the increase in clotrimazole-induced MRP3 reporter activity was suppressed by PXR overexpression (Fig.…”
Section: Discussionmentioning
confidence: 48%